The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1039/c8cc05601c
|View full text |Cite
|
Sign up to set email alerts
|

Oxidant-free oxidative gold catalysis: the new paradigm in cross-coupling reactions

Abstract: The construction of C-C and C-X (X = hetero atom) bonds is the core aspect for the assembly of molecules. In this regard, late transition-metal-catalyzed cross-coupling reactions have retained their dominance for decades. Lately, gold catalysts have been emerging as a reliable contender for such transformations owing to the recent findings that reveal gold's potential beyond carbophilic π-Lewis acid. The newfound ability of gold to undergo redox transformations under certain circumstances has allowed us to exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
60
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(62 citation statements)
references
References 214 publications
2
60
0
Order By: Relevance
“…In the latter case, diazonium salts have been the electrophiles of preference. [4] In initial reports on the use of diazonium salts, the Au I oxidation proceeded via at wo single-electron oxidation mechanism, mediated by ap hotocatalyst under irradiation. More recently, alternative protocolst hat avoid the use of ap hotocatalyst have been developed.…”
Section: Introductionmentioning
confidence: 99%
“…In the latter case, diazonium salts have been the electrophiles of preference. [4] In initial reports on the use of diazonium salts, the Au I oxidation proceeded via at wo single-electron oxidation mechanism, mediated by ap hotocatalyst under irradiation. More recently, alternative protocolst hat avoid the use of ap hotocatalyst have been developed.…”
Section: Introductionmentioning
confidence: 99%
“…Bourissou, Amgoune, and co‐workers and our group have shown that Au I systems modified with appropriate ligands are effective for hitherto unknown Ar−X (X=I, Br) oxidative additions . In addition to these thermal pathways, significant progress has also been made in oxidative addition at gold using photochemically activated routes . In part, such oxidative addition steps are challenging because of the high energy barrier associated with the Au I /Au III redox couple ( E red °: Au III/I =1.41 V vs. Pd II/0 =0.92 V) .…”
Section: Methodsmentioning
confidence: 99%
“…[2][3][4] In addition to these thermal pathways, significant progress has also been made in oxidative addition at gold using photochemically activated routes. [5,6] In part, such oxidative addition steps are challenging [7] because of the high energy barrier associated with the Au I /Au III redox couple (E red 8: Au III/I = 1.41 V vs. Pd II/0 = 0.92 V). [8] Catalysts that can overcome this are significant because they dispense with the highly reactive external [9] or internal [10] oxidants typically required in Aumediated cross-couplings.…”
mentioning
confidence: 99%
“…If the reaction is carried out in the absence of a light source, the N 2 ‐unit from the diazonium salt is retained and azobenzofurans are formed in moderate to high yields. Stoichiometric experiments demonstrate that these products are accessible from the same vinyl Au I intermediate and lead us to propose that the often suggested photochemical oxidative addition either occurs after the formation of a vinyl Au I species or may even not involve oxidation state changes.…”
Section: Methodsmentioning
confidence: 99%